(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Abstract presents the result of the use of prenatal articles for predicting neurological outcomes in preterm labor using ultrasound Doppler studies. Currently, it is obvious that not only the development of examination of premature infants, but also algorithms for antenatal assessment of the state of the fetal brain to predict unfavorable neurological outcomes is evident. Morphological ultrasound and Doppler characteristics of the CNS have been identified against the background of threatening preterm birth, depending on the gestational age at the time of birth, and subsequent neurological disorders of premature babies. The most indicative were changes in the Ventriculo-cranial index, the width of the anterior horns of the lateral ventricles of the brain, thalamo-occepetal size, SD of the vessels of the vertebrobasilar basin of the brain. Similar detailed perinatal diagnostics contributes to non-invasive prediction of the degree of neurological damage to the central nervous system of premature infants.